Potential use of isosorbide dinitrate As a new drug for tilt table test of young adult subject: A study of haemodynamic effects (Medical Journal of Indonesia, 2006)
Vasovagal syncope is a common health problem in young adult population. Tilt table test (TTT) is the only method to diagnose vasovagal syncope. Since isoprenaline as a standard provocative drug of TTT is hard to be found in Indonesia, we study the haemodynamic effect of isosorbide dinitrate (ISDN) which has similar venous pooling effect with isoprenaline. Seventeen young healthy adult subjects (age of 28.6 ± 4.7 year old, and 14 males) underwent TTT using 400 μg ISDN spray sublingually as a provocative drug. The haemodynamic changes were observed during baseline and provocative phase. None of 17 subjects experienced of syncope. Although, the systolic, diastolic, and mean arterial blood pressure were significantly decreased and the heart rate significantly increased after ISDN administration, but the changes were not sufficient to cause syncopal event. In conclusion sublingual ISDN spray during TTT of young healthy adult subject changes haemodynamic measures but did not cause syncope. These results give a reasonable basic for ISDN usage as provocative drug of TTT. (Med J Indones 2006; 15:24-9) Keywords: Syncope, vasovagal, tilt table test, nitrate